RELATIONSHIP BETWEEN WORKLOAD PERCEPTION WITH NURSE BURNOUT LEVEL IN PKU MUHAMAMDIAH HOSPITAL SRAGEN DURING THE COVID-19 PANDEMIC - Ika Silvitasari; Norman Wijaya Gati; Hermawati (P3M Universitas 'Aisyiyah Surakarta, 2023)
Background: During the COVID-19 pandemic, nurses were faced with an increasingly heavy workload, where the number of confirmed patients increased, the number of nurses on duty was confirmed positive and the use of complete personal protective equipment. The heavier workload is one of the trigger factors for burnout. Objective: to determine the relationship between perceived workload and nurse burnout level at PKU Muhamamdiyah Hospital Sragen during the covid 19 pandemic. Methods: the research method is a quantitative cross-sectional approach with sampling techniques using a total sample and getting a total sample of 47 respondents. The instrument used to measure perceived workload was using the NASA TLX Questionnaire and nurse burnout was measured using the Maslach Burnout Inventory-Human Services (MBI-HS) Scale. Results: statistical analysis test using Spearman rank with a significance level of 95%, obtained p value = 0.035 or (p <0.05), so it was found that there was a relationship between perceived workload and nurse burnout level at PKU Muhamamdiyah Hospital Sragen during the covid 19 pandemic. Conclusion: Nurses with a heavy burden will trigger burnout syndrome. Suggestion: conduct further research on interventions to nurses who have high burnout rates.